2013
DOI: 10.1016/j.bbabio.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Allophycocyanin and phycocyanin crystal structures reveal facets of phycobilisome assembly

Abstract: X-ray crystal structures of the isolated phycobiliprotein components of the phycobilisome have provided high resolution details to the description of this light harvesting complex at different levels of complexity and detail. The linker-independent assembly of trimers into hexamers in crystal lattices of previously determined structures has been observed in almost all of the phycocyanin (PC) and allophycocyanin (APC) structures available in the Protein Data Bank. In this paper we describe the X-ray crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 48 publications
2
50
0
Order By: Relevance
“…The shape of the density maps of the PC trimer was similar to that of the APC trimer with a small difference due to an additional loop in the PC [17] that can be distinguished in the density map (dashed circles for Rb-1 in Figure 3B). A typical rod cylinder in our reconstruction contains two PC hexamers associated with two Pfam00427 domains and two Pfam01383 domains.…”
Section: Core and Rod Assemblymentioning
confidence: 80%
See 1 more Smart Citation
“…The shape of the density maps of the PC trimer was similar to that of the APC trimer with a small difference due to an additional loop in the PC [17] that can be distinguished in the density map (dashed circles for Rb-1 in Figure 3B). A typical rod cylinder in our reconstruction contains two PC hexamers associated with two Pfam00427 domains and two Pfam01383 domains.…”
Section: Core and Rod Assemblymentioning
confidence: 80%
“…The crystal structures of some isolated components of PBSs from different species have been determined. These include PEs [12,13], PCs [8,[14][15][16][17], APCs [10,[17][18][19], and linker proteins [10,20] (Supplementary information, Figure S1). The structural layouts of various PBSs have also been suggested in electron microscopic images [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The overall geometry of the PCB chromophores in all light-harvesting phycobiliproteins is ZZZasa (ref. 31 and references therein; nomenclature is provided in Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…PC rods stabilize OCP binding to PBs (Gwizdala et al, 2011), and species-specific changes of this connection could lead to different affinities for the OCP. It was recently shown that a more or less pronounced cavity exists between the APC trimers (Marx and Adir, 2013). This could influence PC rod binding or OCP attachment, but a systematic crystallographic study is needed for verification.…”
Section: Influence Of Pb Structure On the Ocp-pb Interactionmentioning
confidence: 99%